Efektifitas Penindakan Pidana Pemilihan Kepala Daerah di Wilayah Kepulauan - Mathias Alubwaman; Revency V. Rugebreght; Y.A. Lewerissa (LPPM Institut Pendidikan Nusantara Global, 2025)
The election of regional heads is carried out based on the principles of direct, general, free, secret, honest, and fair elections, through a democratic and inclusive process, which is a mandate of the law and must be carried out by every citizen. As stated in the vision and mission statements of the candidates throughout the campaign, the public is expected to be able to make their choice based on their conscience and free from the influence of irresponsible parties. However, this hope is in stark contrast to the reality, with numerous violations committed by the candidates and their campaign teams, as well as by the public itself. Existing regulations and the presence of oversight bodies have not been able to effectively take action against alleged crimes, particularly in island regions. There is still room in the regulations that parties can exploit to evade law enforcement efforts, particularly regarding the Bawaslu's three-calendar-day timeframe for handling criminal violations, plus two days if additional information is needed. The availability of human resources within the supervisory ranks is also important to analyze. This study aims to determine the effectiveness of law enforcement against criminal acts in regional head elections in the archipelago. This study uses normative research methods, namely legal research with a statutory approach and a conceptual approach. The research results show that the effectiveness of criminal prosecution in regional head elections in archipelagic regions is influenced by legal regulations/laws, the behavior of election participants and community culture, and the realities of the archipelagic region. This research demonstrates that in formulating legislation, it is mandatory to consider all aspects, especially those related to the effectiveness of the implementation of the law.